Comparative Analysis of Efforts to Prevent Sexual Violence and Legal Protection for Women in the Criminal Code and Sexual Violence Crime Law (UU NO. 12 of 2022) - T. Riza Zarzani N; Tanjung, Indra Utama; Siti Annisa (International Journal of Synergy in Law, Criminal, and Justice, 2024)
Sexual violence in Indonesia is an increasing issue, as data from the National Commission on Violence Against Women in Annual Records (CATAHU) shows. This research focuses on a comparative analysis between the Criminal Code (KUHP) and Law no. 12 of 2022 concerning Criminal Sexual Violence (UU TPKS) in the context of preventing and protecting women from sexual violence. This research is important considering the high rate of sexual violence and the lack of effective legal protection for victims, especially women. This research also examines how these two regulations contribute to women's autonomy over their bodies and sexuality.This research uses a normative legal method with a descriptive analytical approach. The focus is a comparative analysis of legal norms in the Criminal Code and the TPKS Law. The data used is secondary, including primary legal materials such as the Criminal Code and the TPKS Law, as well as secondary and tertiary legal materials including books, journals and scientific articles. The analysis was carried out descriptively qualitatively to interpret the data and draw relevant conclusions. Legislative and comparative approaches make it possible to evaluate the effectiveness and fairness of existing regulations in the context of preventing sexual violence and legal protection for women.Research Results Legal protection for women from sexual violence in Indonesia is regulated by Law (UU) Number 12 of 2022 concerning the Crime of Sexual Violence, which provides a legal framework for preventing, handling, protecting and recovering victims. This includes intergovernmental coordination and community engagement. The 1945 Constitution and the Human Rights Law also provide a legal basis for the protection of victims. The Criminal Code contains articles related to sexual violence, including rape and obscenity. The Law on the Elimination of Domestic Violence and Child Protection provides additional legal protection. The PPPA Ministerial Regulation also provides regulations for the protection of women and children. The TPKS Law, as a response to increasing sexual violence, regulates nine types of criminal acts of sexual violence with details of criminal penalties and fines. This includes non-physical and physical sexual harassment, forced contraception, forced sterilization, forced marriage, sexual torture, sexual exploitation, sexual slavery, and electronic-based sexual violence.The old Criminal Code and Law no. 1 of 2023 concerning the new Criminal Code also regulates obscene acts. Proving sexual harassment in criminal law uses five types of evidence according to the Criminal Procedure Code. Efforts to increase the implementation of the TPKS Law depend on the understanding and professionalism of law enforcement officials, as well as improving key factors in law enforcement.Keywords: Prevention of Sexual Violence, Legal Protection of Women, Criminal Code vs TPKS Law